STATISTICAL MODELING OF RANDOM PROCESS AND TWO- DIMENSION FIELDS ON EXAMPLE OF AEROMAGNETIC DATA - Vyzhva, Z.; Demidov, V.; Vyzhva, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
To solve the problems of conditional maps, adding of data to achieve the necessary precision, and other such problems in geophysics, it is proposed to apply methods of statistical simulation of realizations of random processes and multi-dimensional random functions (random fields). For data analysis, it is proposed to be divided into deterministic and random components. To separate the deterministic component is proposed approximation of data by cubic splines. The stationary random component is ξk(x) is proposed to modeling on the basis of spectral expansions of random functions. Model example – aeromagnetic data.